The Gut Microbial Community Structure of the North American River Otter (Lontra canadensis) in the Alberta Oil Sands Region in Canada: Relationship with Local Environmental Variables and Metal Body Burden. (28th October 2020) - Guo, Galen; Eccles, Kristin M.; McMillan, Morgan; Thomas, Philippe J.; Chan, Hing Man; Poulain, Alexandre J.
Abstract: The Alberta Oil Sands Region in Canada is home to one of the largest oil bitumen deposits in the world. The North American river otter ( Lontra canadensis ) is a top predator with a small home range and is sensitive to disturbances; it has been designated as a sentinel species for the potential impacts of the natural resource exploitation on freshwater ecosystems in the Alberta Oil Sands Region. With an increasing interest in noninvasive biomarkers, recent studies suggest that gut microbiota can be used as a potential biomarker of early biological effects on aquatic wildlife. The goal of the present study was to determine the river otter gut microbial structure related to environmental variables characterizing mining activities and metal body burden. We obtained 18 trapped animals from and surrounding the surface mineable area of the Alberta Oil Sands Region. The gut microbial community structure was characterized using high‐throughput sequencing of 16S rRNA gene amplicon analyses. Trace metal concentrations in the liver were measured by inductively coupled plasma–mass spectrometry. Our study revealed that the gut bacteria of river otters in the Alberta Oil Sands Region clustered in 4 groups dominated by Peptostreptococcaceae, Carnobacteriaceae, Enterobacteriaceae, Clostridiaceae, and Nostocaceae. We show that arsenic, barium, rubidium, liver‐body weight ratio, and δ 15 N were associated with each cluster. When comparing affected versus less affected sites, we show that river otter gut bacterial community and structure are significantly related to trophic level of the river otter but not to Alberta Oil Sands Region mining activities. Our study reveals that the gut bacterial dynamics can provide insights into the diet and habitat use of river otters but that more work is needed to use it as a pollution biomarker. Environ Toxicol Chem 2020;39:2516–2526. © 2020 SETAC